Prognostic value of the preoperative prognostic nutritional and systemic immunoinflammatory indexes in patients with colorectal cancer - Haifeng Li; Wei Sun; Shengfeng Fu; Junfeng Wang; Bin Jin; Shuo Zhang; Yujun Liu; Qinyang Zhang; Honggang Wang (BMC Cancer)
Abstract Introduction Colorectal cancer (CRC) is a common malignant tumor of the digestive tract. Although many prognostic indicators are currently available, it remains unclear which indicators are the most beneficial for patients with CRC. Therefore, there is a critical need to identify a simple, convenient and accurate prognostic indicator. Purpose To investigate the clinical significance of the systemic immune-inflammation index (SII) and prognostic nutritional index (PNI) as prognostic indicators for the survival of patients with CRC. Methods The clinical data of CRC patients admitted to the general surgery ward of Taizhou People’s Hospital affiliated to Nanjing Medical University from January 2015 to January 2018 were retrospectively analyzed. Two prognostic indicators (SII and PNI) were compared to evaluate their prognostic value in CRC patients. Results Based on these variables, we constructed a LASSO prediction model. The AUC (Area Under the Curve) value and 95% CI of the training group were 0.917 (0.858–0.976) compared to 0.932 (0.846–1.000) in the validation group. We found that CEA > 5 ng/mL, tumor stage, pathological type, postoperative complications, and PNI were associated with the five-year survival rate of CRC patients. Receiver Operating Characteristic Curves (ROC) were drawn to assess the prediction accuracy of the model. The AUC and 95% CI of the training group were 0.913 (0.854–0.972), while the AUC and 95% CI of the validation group were 0.954 (0.899–1.000). Conclusions PNI is an independent risk factor for postoperative complications associated with CRC and a powerful tool for predicting survival outcomes in CRC patients.